Analysis of VAT Policy Toward Overseas Digital Service Providers Through Consumer Regulatory Impact Assessment in Indonesia - Cherly Elisabeth (Golden Ratio of Taxation Studies, 2023)
This study aims to examine the extent to which PMK No. 60/PMK.03/2022 is said to meet international standards through Regulatory Impact Assessment in the guidelines of the Organization for Economic Co-operation and Development. This research applies qualitative research with a case study approach. The data in this study are qualitative data sourced from interviews (primary data), observation, and documentation (secondary data). Data analysis was conducted in several stages, namely data collection, data refinement, data processing, data analysis, and conclusion drawing, as well as ten RIA question steps as a measuring tool. The results showed that both PMK 48/2020 and PMK 60/2022 have answered the ten Steps of RIA questions well, but the distribution of benefits to the community still needs to be elaborated in order to increase transparency. Furthermore, easy access to the draft policy of PMK 60/2022 so that the government's intentions and objectives for enacting the policy are clear and understood by the public.